Is maternal education associated with childhood overweight risk? Trends between 2010 and 2013- the COSI Portugal study - Baleia, Joana (2017)
Introduction: Considerable inequalities in overweight and obesity are evident among European children. Particularly in Portugal, a country with one of the highest prevalence of childhood obesity, understanding the most relevant socioeconomical factors such as maternal education, is crucial to promote children's immediate health and well-being throughout life course.